EFFECT OF SOME PROPOGATION METHODS IN GROWTH OF - Muthafar O. Abdullah (Mesopotamia Journal of Agriculture)
This study was carried out at Ninevah plantation Nursery in Mosul city, during the period from mid January to the end of October (1999) to investigate the effect of four collection times, and four cutting lengths, Using tow planting methods (Vertical and Horizontal) in propagation of Salix seedlings. This experiment was conducted as factorial experiment in Randomized completely Block Design with three factors and three blocks. Several growth and propagation traits was studies. The result showed that the collection cutting time (15 February), cutting length (30 cm.) and that vertical planting method were the best, it gave higher means for all studied characteristics. The result also showed that the following interactions between (collection cutting time 15 February and cutting length 30 cm.), (collection cutting time 15 February and vertical planting method), (cutting length 30 cm. and vertical planting method) and (collection cutting time 15 February and cutting length 30 cm. and vertical planting method) was the best among other interactions.